2012
DOI: 10.1039/c2mt20059g
|View full text |Cite
|
Sign up to set email alerts
|

Multiple forms of selenoprotein P in a candidate human plasma standard reference material

Abstract: Selenoprotein P (SePP) is a unique selenium-containing protein responsible for the transport and distribution of the essential trace element selenium (Se) through the human body with the concentration of SePP in human blood representing the most useful marker of Se nutritional status. Although SePP has been extensively studied, the structure of SePP in human plasma remains unresolved. Two potential isoforms of SePP have been identified by Western blot analyses distinguished principally by differences in migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
1
24
0
1
Order By: Relevance
“…There the reliability of our SePP determination was verified since the immunologically determined SePP concentration in a pooled CSF sample was 0.54 nM/l (±9.5%) with SePP being expressed as total protein. According to the literature data regarding SePP (10 Se atoms per SePP and molecular weight MW(SePP) = 61 kDa [32]) this SePP-protein concentration refers to 0.43 ± 0.04 g Se/l at SePP corresponding well to our value at 0.41 ± 0.01 g Se/l at SePP peak. Thus our method was verified by an independent reference method.…”
Section: Laboratory Analysissupporting
confidence: 85%
“…There the reliability of our SePP determination was verified since the immunologically determined SePP concentration in a pooled CSF sample was 0.54 nM/l (±9.5%) with SePP being expressed as total protein. According to the literature data regarding SePP (10 Se atoms per SePP and molecular weight MW(SePP) = 61 kDa [32]) this SePP-protein concentration refers to 0.43 ± 0.04 g Se/l at SePP corresponding well to our value at 0.41 ± 0.01 g Se/l at SePP peak. Thus our method was verified by an independent reference method.…”
Section: Laboratory Analysissupporting
confidence: 85%
“…Accordingly, in the MS/MS-based analyses of the reference plasma SRM1950 of the U.S. population, three SELENOP molecules of 57, 49 and 45 kDa were identified [18]. Alternatively, slightly shortened SELENOP isoforms may result from a specific limited proteolysis within the Se-rich C-terminus [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are indications that the circulating SELENOP is not a homogenous protein. Variants of different molecular weight have been described [13], [18], in relation to genotype, premature translational termination, limited posttranslational proteolysis or partial replacement of Sec by Cys [19], [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…120 A recent study reported the separation and characterization of three distinct SelP isoforms also in human plasma, with Mw of 45, 49 and 57 kDa, the first being a truncated isoform lacking in Se. 121,122 SelP is mainly produced in the liver and then secreted into the plasma, where it incorporates the major part of Se, but it is expressed and probably secreted also by other tissues including the brain and the heart. As mentioned in Section 3.3, evidence supports functions of SelP in Se transport and homeostasis throughout the whole body.…”
Section: Selenoprotein Tmentioning
confidence: 99%